2011
DOI: 10.5194/bgd-8-10017-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Annual emissions of CH<sub>4</sub> and N<sub>2</sub>O, and ecosystem respiration, from eight organic soils in Western Denmark managed by agriculture

Abstract: The use of organic soils by agriculture involves drainage and tillage, and the resulting increase in C and N turnover can significantly affect their greenhouse gas balance. This study estimated annual fluxes of CH4 and N2O, and ecosystem respiration (Reco), from eight organic soils managed by agriculture. The sites were located in three regions representing different landscape types and climatic conditions, and three land use categories (arable crops, AR, grass in rotati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 42 publications
1
34
1
Order By: Relevance
“…, a summer crop with bare soil before and after cropping. On the contrary, a fen in Denmark, cultivated with barley undersown by grass, revealed a higher cumulated annual R eco than our cropland site ( Elsgaard et al, 2012; Petersen et al, 2012). The difference between the Danish studies was possibly also due to a higher autotrophic respiration of the under sown grass compared to the system without under seed.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…, a summer crop with bare soil before and after cropping. On the contrary, a fen in Denmark, cultivated with barley undersown by grass, revealed a higher cumulated annual R eco than our cropland site ( Elsgaard et al, 2012; Petersen et al, 2012). The difference between the Danish studies was possibly also due to a higher autotrophic respiration of the under sown grass compared to the system without under seed.…”
Section: Discussioncontrasting
confidence: 63%
“…Nevertheless, there are few direct measurements of greenhouse gas emissions from arable fens ( Maljanen et al, 2007), especially on deeply drained temperate fens, using the chamber technique ( Petersen et al, 2012; Elsgaard et al, 2012; Kandel et al, 2013). Most studies were either conducted for a time period of only one or two years or not all three GHGs were considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was considered doubtful to treat the present organic soils according to the fixed IPCC EF, because the definitions of organic soils in the Danish JB (jordbonitet) soil classification system and the IPCC guidelines are very different: in the Danish system, soils are classified as organic if they have a soil organic carbon (SOC) content higher than 5.9% (Greve & Breuning-Madsen, 2005), whereas the IPCC definition of organic soils (IPCC, 2006) implies a SOC content higher than 12% (this latter definition applies to soils that are never saturated with water for more than a few days). Thus, whereas high N 2 O emissions have indeed been found for Danish agricultural peat soils (with 16Á47% SOC in the top soil; Petersen et al, 2012), the area of such soils is much lower than suggested from the occurrence of soils classified as organic in Denmark …”
Section: Regionmentioning
confidence: 62%
“…Whilst no heterogeneity was found across studies, the studies by Petersen et al [40] showed much higher variability than the other two studies, possibly because they used nationwide survey data rather than site-based experimental comparisons. The Petersen et al [40] studies were classed as 'unclear' in their susceptibility to bias, and more information on the methodology Figure 14 Forest plot of meta-analysis of effect sizes (raw mean difference) comparing N 2 O flux from wet versus dry peatlands. The dashed line represents no effect.…”
Section: Farmland Interventions High Intensity Farmed-vs-low Intensitmentioning
confidence: 80%